2007
DOI: 10.1158/0008-5472.can-06-3546
|View full text |Cite
|
Sign up to set email alerts
|

Clioquinol, a Therapeutic Agent for Alzheimer's Disease, Has Proteasome-Inhibitory, Androgen Receptor–Suppressing, Apoptosis-Inducing, and Antitumor Activities in Human Prostate Cancer Cells and Xenografts

Abstract: Tumor growth and metastasis depend on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
169
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(179 citation statements)
references
References 40 publications
4
169
1
3
Order By: Relevance
“…[22][23][24][25][26][27][28][29] It has long been established that inhibition of the proteasome prevents activation of NFκB by stabilizing the phosphorylated form of IκBα that is still bound to the NFκB heterodimer, retaining it in the cytoplasm. 30 Western blot analysis of lysates prepared from cells treated with the well-described proteasome inhibitor lactacystine 31 revealed a prolonged IκBα phosphorylation following TNF induction, consistent with impaired IκBα degradation (Fig.…”
Section: Copper Blocks Nfκb Nuclear Translocationmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] It has long been established that inhibition of the proteasome prevents activation of NFκB by stabilizing the phosphorylated form of IκBα that is still bound to the NFκB heterodimer, retaining it in the cytoplasm. 30 Western blot analysis of lysates prepared from cells treated with the well-described proteasome inhibitor lactacystine 31 revealed a prolonged IκBα phosphorylation following TNF induction, consistent with impaired IκBα degradation (Fig.…”
Section: Copper Blocks Nfκb Nuclear Translocationmentioning
confidence: 99%
“…To test this, we mixed CQ and CuCl 2 in a 1:1 molar ratio and an observable color change occurred, indicating that a chemical reaction had taken place (136). This was further confirmed by the use of X-ray absorption near-edge spectroscopy (XANES) and extended X-ray absorption fine structure spectroscopy (EXAFS), which showed that the CQ-Cu mixture had a different copper oxidation state than CQ or CuCl 2 alone, which verified that a coordination complex with copper had indeed been formed (136).…”
Section: Clioquinolmentioning
confidence: 99%
“…CQ-Cu (1:1 ratio) inhibits purified 20S proteasome (IC 50 =2.5 µM), as well as intact cellular proteasome in C4-2B and LNCaP prostate cancer cells. In addition to inhibition of proteasomal activity, CQ-Cu suppressed androgen receptor expression, inhibited cellular proliferation and induced apoptosis in these cells [28]. In C4-2B xenograft-bearing mice, tumour growth was significantly suppressed (66%) following CQ treatment, and proteasome inhibition was also evident [28].…”
mentioning
confidence: 99%
“…Clioquinol (5-chloro-7-iodo-8-hydroxyquinoline, CQ), is a lipophilic compound that is currently used to treat Alzheimer's and Huntington's diseases [27] and is able to form stable complexes with copper(II) [28]. CQ-Cu (1:1 ratio) inhibits purified 20S proteasome (IC 50 =2.5 µM), as well as intact cellular proteasome in C4-2B and LNCaP prostate cancer cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation